2011
DOI: 10.1111/j.1468-3083.2011.04386.x
|View full text |Cite
|
Sign up to set email alerts
|

Daylight photodynamic therapy for actinic keratosis: an international consensus

Abstract: Photodynamic therapy (PDT) is an attractive therapy for non-melanoma skin cancers including actinic keratoses (AKs) because it allows treatment of large areas; it has a high response rate and results in an excellent cosmesis. However, conventional PDT for AKs is associated with inconveniently long clinic visits and discomfort during therapy. In this article, we critically review daylight-mediated PDT, which is a simpler and more tolerable treatment procedure for PDT. We review the effective light dose, efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
194
0
12

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(209 citation statements)
references
References 23 publications
3
194
0
12
Order By: Relevance
“…Instead of a long incubation with a short illumination (c-PDT), daylight-PDT is performed with a short incubation and long illumination. More precisely, while during c-PDT a high amount of PpIX accumulates and is excited within short time, DL-PDT relies on the constant production and excitation of PpIX molecules within 2 h. Therefore a microphototoxic effect is postulated for DL-PDT, in contrast to a massive phototoxic effect induced by c-PDT [96,97].…”
Section: Pdt With Natural and Simulated Daylightmentioning
confidence: 99%
“…Instead of a long incubation with a short illumination (c-PDT), daylight-PDT is performed with a short incubation and long illumination. More precisely, while during c-PDT a high amount of PpIX accumulates and is excited within short time, DL-PDT relies on the constant production and excitation of PpIX molecules within 2 h. Therefore a microphototoxic effect is postulated for DL-PDT, in contrast to a massive phototoxic effect induced by c-PDT [96,97].…”
Section: Pdt With Natural and Simulated Daylightmentioning
confidence: 99%
“…As daylight PDT requires exposure of the affected skin to daylight, the treatment is most suitable for lesions and areas of actinic damage on the face and scalp 12. Findings from a subgroup analysis of AK severity showed that following daylight PDT, lesion response rates of thin AK (76% [1572 lesions at baseline]) were higher than with moderate or thick AK (61% (974 lesions at baseline), 49% (222 lesions at baseline), as is also the case with c‐PDT and other topical treatments 14.…”
Section: Whom To Treat With Daylight Pdt With Methyl Aminolevulinate mentioning
confidence: 99%
“…International consensus recommendations for daylight PDT for treatment of AK have been developed primarily by and for dermatologists in Europe and Canada 12. Since this consensus, a phase III study has been performed in Australia confirming the efficacy and tolerability of daylight PDT 13.…”
Section: Introductionmentioning
confidence: 99%
“…The daylight PDT allows patients to be active and under the sun during treatment, contrary to illumination with a fixed wavelength in clinical place [42,43]. Daylight PDT has a good efficiency and is less painful thanks to low light output compared to the conventional method.…”
Section: Photomedicine -Advances In Clinical Practicementioning
confidence: 99%